THE ASSESSMENT OF THE VIRTUAL LEARNING ENVIRONMENT: PERCEPTIONS OF INDONESIAN COLLEGE STUDENTS - Herdi Herdi (JIV-Jurnal Ilmiah Visi, 2024)
The research aims to explore the factors structure of the virtual learning environment based on the perspective of Indonesian college students. The study used a descriptive method of survey type. The sample amounted to 511 college students from one of the state universities in Indonesia who were selected using incidental sampling techniques. The data were collected using an Indonesian version of the Technology-Rich Outcomes-Focused Learning Environment Inventory (TROFLEI) with excellence of psychometric properties. The data were analysed using descriptive statistics and confirmatory factor analysis assisted by SPSS v. 26 for Windows. The findings show that there are 10 dimensions of the virtual learning environment based on the perspective of Indonesian college students, namely: computer usage, student involvement, young adult ethos, task orientation, investigation, lecturer support, cooperation, equity, cohesivity, and differentiation. Further studies are needed to examine the factors structure of the virtual learning environment using confirmatory factor analysis with LISREL and examine their antecedents and consequences to academic performance and achievement in a wider range of college students taking into account their ethno-socio-demographic proportions in Indonesia.